Determining health index of transmission line asset using condition-based method - Hashim R.; Usman F.; Baharuddin I.N.Z. (MDPI AG, 2023)
Assessment of overhead transmission lines is a crucial task in the asset management of electric power infrastructures. Any assets have different life spans and require proper assessment and maintenance actions. Disruption of the power supply may cause national problems. Therefore, it is essential to ensure that the distribution and transmission of electric power from the power plant to end consumers is achieved without fail. This paper presents a proposed framework of health index of the transmission line using a condition-based method. This study refers to previous methods in determining the health index of electrical power assets, mainly transformer and transmission line. Three main indicators contributed and need to be considered in determining the health index. The indicators are structural, electrical and environmental aspects. The health index of these three indicators with 14 items was calculated, and the overall health index of the transmission line determined. From the case study conducted for this study, the specific location, tower and item can be acknowledged that cause the failure and the service interruption of energy supply to the consumer. It is found that the implementation of the health index calculation gives a more accurate description of the health status of a transmission line. The health index can be used for the prioritizing of maintenance, refurbishment or replacement to avoid disruption. 2019 by the authors.